An integrative model of the control of ovule primordia formation. (19th September 2013) - Galbiati, Francesca; Sinha Roy, Dola; Simonini, Sara; Cucinotta, Mara; Ceccato, Luca; Cuesta, Candela; Simaskova, Maria; Benkova, Eva; Kamiuchi, Yuri; Aida, Mitsuhiro; Weijers, Dolf; Simon, Rüdiger; et al.
Summary Upon hormonal signaling, ovules develop as lateral organs from the placenta. Ovule numbers ultimately determine the number of seeds that develop, and thereby contribute to the final seed yield in crop plants. We demonstrate here that CUP‐SHAPED COTYLEDON 1 (CUC1), CUC2 and AINTEGUMENTA (ANT) have additive effects on ovule primordia formation. We show that expression of the CUC1 and CUC2 genes is required to redundantly regulate expression of PINFORMED1 (PIN1), which in turn is required for ovule primordia formation. Furthermore, our results suggest that the auxin response factor MONOPTEROS (MP/ARF5) may directly bind ANT, CUC1 and CUC2 and promote their transcription. Based on our findings, we propose an integrative model to describe the molecular mechanisms of the early stages of ovule development.